Isotropization at small scales of rotating helically driven turbulence - Mininni, Pablo Daniel (2012)
We present numerical evidence of how three-dimensionalization occurs at small scale in rotating turbulence with Beltrami (ABC) forcing, creating helical flow. The Zeman scale ℓ Ω at which the inertial and eddy turn-over times are equal is more than one order of magnitude larger than the dissipation scale, with the relevant domains (large-scale inverse cascade of energy, dual regime in the direct cascade of energy E and helicity H, and dissipation) each moderately resolved. These results stem from the analysis of a large direct numerical simulation on a grid of 3072 3 points, with Rossby and Reynolds numbers, respectively, equal to 0.07 and 2.7 × 10 4. At scales smaller than the forcing, a helical wave-modulated inertial law for the energy and helicity spectra is followed beyond ℓ Ω by Kolmogorov spectra for E and H. Looking at the two-dimensional slow manifold, we also show that the helicity spectrum breaks down at ℓ Ω , a clear sign of recovery of three-dimensionality in the small scales. © 2012 Cambridge University Press.